Proximal adductor avulsions are rarely isolated but usually involve injury to the PLAC and pectineus: descriptive MRI findings in 145 athletes - Schilders, E; Mitchell, AWM; Johnson, R; Dimitrakopoulou, A; Kartsonaki, C; Lee, JC (Springer, 2020)
Purpose The purpose of the study is to review the MRI findings in a cohort of athletes who sustained acute traumatic avulsions of the adductor longus fibrocartilaginous entheses, and to investigate related injuries namely the pyramidalis–anterior pubic ligament–adductor longus complex (PLAC). Associated muscle and soft tissue injuries were also assessed. Methods The MRIs were reviewed for a partial or complete avulsion of the adductor longus fibrocartilage, as well as continuity or separation of the adductor longus from the pyramidalis. The presence of a concurrent partial pectineus tear was noted. Demographic data were analysed. Linear and logistic regression was used to examine associations between injuries. Results The mean age was 32.5 (SD 10.9). The pyramidalis was absent in 3 of 145 patients. 85 of 145 athletes were professional and 52 competed in the football Premier League. 132 had complete avulsions and 13 partial. The adductor longus was in continuity with pyramidalis in 55 athletes, partially separated in seven and completely in 81 athletes. 48 athletes with a PLAC injury had a partial pectineus avulsion. Six types of PLAC injuries patterns were identified. Associated rectus abdominis injuries were rare and only occurred in five patients (3.5%). Conclusion The proximal adductor longus forms part of the PLAC and is rarely an isolated injury. The term PLAC injury is more appropriate term. MRI imaging should assess all the anatomical components of the PLAC post-injury, allowing recognition of the different patterns of injury. Level of evidence Level III.